Using media to promote suicide prevention hotlines to Veteran households. Issue 1 (24th May 2013) - Karras, Elizabeth; Stephens, Brady; Kemp, Janet E; Bossarte, Robert M
Abstract : This article presents preliminary evidence that media campaigns are valuable in promoting suicide prevention hotlines to Veteran households by reporting data from 2526 telephone surveys. Findings from this study underscore the need for further investigation of the use of media campaigns to support suicide prevention initiatives aimed at Veteran populations.